Preliminary Evaluation of Sound Insulation Capability in Wood-Based Materials Using Realistic Noise Sources under a Simplified Experimental Approach - Wahyuningtyas, Irma; Syafi'i; Kutana, Agung Nugrawan (Science Education and Application Journal, 2026)
This study evaluates the sound attenuation capabilities of four wood-based materials under realistic noise conditions. An experimental approach using a simple, non-standardized test method was conducted in a small-scale chamber, where each material was alternately installed as a barrier. Sound sources included motorcycle horns, falling objects, woodworking machines, and music. Sound intensity was measured using a sound level meter, and each treatment was repeated three times. The data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that all tested materials significantly reduced sound intensity compared to the control (P < 0.05), with the average sound intensity value ranging from 74.6 to 89.6 dB. Statistical analysis confirmed significant differences among materials. In conclusion, wood-based materials demonstrate the ability to reduce sound intensity under practical noise conditions, with particle board showing the best performance, and solid wood showing the lowest performance. Although the method used is simple and not based on standardized acoustic testing, the results provide preliminary evidence of the potential of porous wood-based materials as sound-absorbing media.